A case report of surgery-radiotherapy-chemotherapy cured primary diffuse large B-cell lymphoma of the central nervous system associated with HIV infection - Qiaoqiao Zhang; Jingzhen Lai; Sufang Ai; Shulin Song; Junjun Jiang; Zhiman Xie (BMC, 2024)
Abstract Background Diffuse large B-cell lymphoma (DLBCL) is one of the most common complications in patients with Acquired Immune Deficiency Syndrome (AIDS), yet its prognosis is generally poor. The impact of surgery on DLBCL remains controversial. We present a case of DLBCL associated with HIV infection, in which the patient achieved complete remission following surgical removal, radiotherapy, and sequential dose-adjusted EPOCH (DA-EPOCH) chemotherapy. Case summary A thirty-year-old man presented with dizziness and headache on September 24, 2019. He had a history of AIDS and pulmonary tuberculosis. He was initially diagnosed with left cerebellar astrocytoma and chronic pneumonia at a local hospital. At our hospital, following magnetic resonance imaging (MRI) and surgical intervention, pathology and immunohistochemistry results indicated DLBCL in the left cerebellar hemisphere. He subsequently underwent resection of the tumor in the left cerebellar hemisphere, received radiotherapy for half a month, and completed sequential DA-EPOCH chemotherapy for seven cycles. His symptoms improved, and the prognosis was favorable, with no signs of recurrence after 4 years of follow-up. Conclusion Surgery is applicable to isolated and superficial lesions. However, it should be combined with radiotherapy and chemotherapy to achieve better treatment.